2015
DOI: 10.4028/www.scientific.net/msf.828-829.366
|View full text |Cite
|
Sign up to set email alerts
|

Development of High Welding Speed in Friction Stir Welded 5182-H111, and the Resulting Influence on down Force

Abstract: In this manuscript the development of the process parameters to friction stir weld 5.15mm thick AA5182-H111 at a feed rate of 1500mm/min is discussed. Compared to a weld made at 200mm/min the weld-pitch had to be reduced from 2.0rev/mm to 0.3rev/mm and down force increased from 27kN to 59kN to create a weld with tensile-and yield strength exceeding that of the parent material, whilst elongation was only marginally reduced. The low weld pitch coupled with the high feed rate resulted in a reduction in the weld t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…In previous work, some of the present authors [1] have demonstrated successful FS welding in 5.15 mm thick plates of 5182-H111 alloy at a linear welding speed of 1.5 m/min. This was made possible by reducing the weld pitch from 2.0 mm/rev at linear welding speeds of 0.2 m/min, to 0.3 mm/rev at a linear welding speed of 1.5 m/min.…”
Section: Introductionmentioning
confidence: 66%
See 4 more Smart Citations
“…In previous work, some of the present authors [1] have demonstrated successful FS welding in 5.15 mm thick plates of 5182-H111 alloy at a linear welding speed of 1.5 m/min. This was made possible by reducing the weld pitch from 2.0 mm/rev at linear welding speeds of 0.2 m/min, to 0.3 mm/rev at a linear welding speed of 1.5 m/min.…”
Section: Introductionmentioning
confidence: 66%
“…As noted above, Bernard et al [1] found increased tensile properties with the 1.5 m/min weld, proposing in a later publication [6] that this was achieved through the high levels of plastic strain. In a review paper by Heidarzadeh et al, [11] presented maps of strain, strain rate and temperature normalized to the melting temperature as a function of the position in the weld, based on results from other studies [12].…”
Section: Strengthening Mechanisms In 5182-h111mentioning
confidence: 81%
See 3 more Smart Citations